2021
DOI: 10.1016/j.uclim.2021.100791
|View full text |Cite
|
Sign up to set email alerts
|

Improved air quality during COVID-19 at an urban megacity over the Indo-Gangetic Basin: From stringent to relaxed lockdown phases

Abstract: The enforced lockdown amid COVID-19 pandemic eased anthropogenic activities across India. The satellite-derived aerosol optical depth (AOD) and absorption AOD showed a significant reduction of ~30% over the Indo-Gangetic Basin (IGB) in north India during the lockdown period in 2020 with respect to the previous year 2019, when no such lockdown was in effect. Further, near-surface air pollutants were investigated at an urban megacity Delhi during 01 March to 31 May 2020. Except O 3 , a dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 57 publications
5
32
0
2
Order By: Relevance
“…A Chinese study reported that comparing outdoor pollutant levels from January 21 to March 23 during the both 2020 and 2019, reported that average PM 2.5 levels fell by an average of 35%, 29%, and 19% respectively in Wuhan, Hubei (Wuhan excluded), and China (Hubei excluded) and NO 2 levels fell by an average of 53%, 50%, and 30% respectively in Wuhan, Hubei, and China respectively (Chu et al 2021 ). During the lockdown period between March 1 to May 31, 2020, mean outdoor levels of PM 10 , PM 2.5 , NO, NO 2 , and CO levels fell by an average of 58%, 47%, 76%, 68 and 58% respectively in Delhi, India, as compared to the 2019 values (Srivastava et al 2021 ). A study in 7 Korean cities reported that mean PM 2.5 levels fell by an average of 7.5 to 24.9% during the 2020 lockdown as compared to 2019 (Kwak et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…A Chinese study reported that comparing outdoor pollutant levels from January 21 to March 23 during the both 2020 and 2019, reported that average PM 2.5 levels fell by an average of 35%, 29%, and 19% respectively in Wuhan, Hubei (Wuhan excluded), and China (Hubei excluded) and NO 2 levels fell by an average of 53%, 50%, and 30% respectively in Wuhan, Hubei, and China respectively (Chu et al 2021 ). During the lockdown period between March 1 to May 31, 2020, mean outdoor levels of PM 10 , PM 2.5 , NO, NO 2 , and CO levels fell by an average of 58%, 47%, 76%, 68 and 58% respectively in Delhi, India, as compared to the 2019 values (Srivastava et al 2021 ). A study in 7 Korean cities reported that mean PM 2.5 levels fell by an average of 7.5 to 24.9% during the 2020 lockdown as compared to 2019 (Kwak et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the emissions of both primary or/and secondary particles can reduce particulate matter content. The primary PM refers to natural and anthropogenic activities such as wind erosion and road traffic in urban areas (Dumka et al 2021 ; Kerimray et al 2020 ; Pei et al 2020 ; Srivastava et al 2021 ), while the two main secondary PM components are nitrate and sulfate, formed in the air from precursors of NO 2 and SO 2 . As a result, the reduction in the emissions of NO 2 and SO 2 could indirectly reduce the secondary ambient PM formation (Tables 3 – 4 and Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, such widespread negative nighttime LST anomaly across Europe and North America cannot be explained only by either small-scale natural variability (local meteorology) or large-scale decadal climate variability (ENSO), and therefore, it has to be apportioned to other sources/causes. Thus, it can be deduced that large-scale nighttime reduction of temperature during the lockdown period was mostly attributed to minimal emissions by human activities ( Srivastava et al, 2021 ) and the weakening of the UHI effect, while it can be also modulated by changes in meteorology, surface characteristics and natural aerosol variability ( Pandey & Vinoj, 2021 ). A 3-D atmospheric numerical modeling approach is required to quantify the contribution of different sectors (transport, industry, etc.)…”
Section: Discussionmentioning
confidence: 99%